Keratin/Hydrotalcites Hybrid Sponges as Promising Adsorbents for Cationic and Anionic Dyes - Posati, Tamara; Listwan, Arthur; Sotgiu, Giovanna; Torreggiani, Armida; Zamboni, Roberto; Aluigi, Annalisa (Frontiers in Bioengineering and Biotechnology, 2020)
In this work, keratin sponges were prepared by freeze-drying method and tested for adsorption of Azure A and Methyl Orange dyes. The obtained materials showed a porosity of 99,92% and a mean pore size dimension of about 91μm. The use of oxidized sucrose with a heating treatment at 150°C was demonstrated to be a useful crosslinking procedure alternative to the conventional glutaraldehyde. Keratin sponges showed a maximum adsorption capacity of 0.063 mmol/g and of 0.037 mmol/g for Azure A and Methyl Orange, respectively. The absorption of the cationic dye AzureA onto keratin sponges was better described by Freundlich model while the isotherm adsorption of the anionic Methyl Orange was found to correlate with both Langmuir and Freundlich models. The mean free energies evaluated by using the D-R model indicated a physisorption of Methyl Orange and a chemisorptions of Azure A onto keratin sponges. Finally, the functionalization of keratin sponges with Zn Al hydrotalcites nanoparticles did not affect the adsorption performances of the adsorbent towards the cationic dye Azure A, while it improved those towards the anionic Methyl Orange, increasing the related removal efficiencies from 43% to 96%. Collectively, the reported data indicates that the combination of keratin with hydrotalcites nanoparticles is a good strategy to obtain more functional adsorbent materials of potential interest for water treatment and purification.